Analysis of the Effect of Print Speed and Layer Height on the Hardness of TPU-95A Filament 3D-Printed Products - Lesmana, Rizal; Mardiyana, Dani; Sumarno, Dodi Iwan (Universitas Negeri Jakarta, 2025)
The effect of print speed and layer height settings can influence the mechanical properties of 3D-printed products; however, the impact of print speed and layer height on the hardness of products printed with TPU-95A filament has not been extensively studied. This research employs an experimental method by creating specimens according to ASTM D2240 standards, using various print speed settings (70, 80, and 90 mm/s) and layer heights (0.15 and 0.20 mm). The results show that a combination of lower print speeds and thinner layer heights yields higher hardness test results. A print speed of 90 mm/s and a layer height of 0.15 mm produced the highest hardness, while the combination of 90 mm/s print speed and 0.2 mm layer height resulted in the lowest hardness. This study contributes to the optimization of 3D printing parameters for flexible material applications, such as TPU-95A, in relation to product hardness outcomes.